Efektivitas Wira Wiri Suroboyo Sebagai Moda Transportasi Publik di Kota Surabaya - Al-haq Naufal Susilo Hadi; Lukman Arif (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Surabaya is a continuously growing economic center, with significant mobility of residents and visitors, necessitating the development of public transportation to enhance mobility in East Java. The transportation needs of an area are generally served by public transport. Recently, the traffic data analysis company from Washington, United States, Inrix, released a study titled the Global Traffic Scorecard 2022, which ranked Surabaya as the most congested city in Indonesia. Wira Wiri Suroboyo was introduced as a public transportation system in Surabaya. The role of Wira Wiri Suroboyo as a feeder transport in Surabaya is expected to be a solution to public transportation issues and a key to expanding public transportation coverage in Surabaya. However, the implementation of Wira Wiri Suroboyo has encountered several issues, including scheduling, infrastructure, and many more. This study aims to determine and analyze the effectiveness of Wira Wiri Suroboyo as a mode of public transportation in Surabaya using Duncan's theory with a qualitative research method and descriptive approach. The research results focus on three dimensions: (1) goal achievement: the results indicate that the sub-dimensions of time frame and specific targets have been effectively achieved, but the sub-dimension of legal sources has not been effective yet, (2) integration: it has been effectively implemented with achievements in both sub-dimensions, namely procedures and socialization, (3) adaptation: the sub-dimension of capacity improvement has been effectively implemented, while the sub-dimension of infrastructure has not been effectively implemented overall. From these results, it can be concluded that Wira Wiri Suroboyo as a mode of public transportation in Surabaya is not yet considered effective overall.